Open Practices for Faculty - Michaela Willi Hooper (Linn-Benton Community College, 2019)
This course is intended to provide a foundation in the skills and knowledge you'll need to create, remix, adopt, or update open educational resources (OER). Specifically, by the end of the course you'll be able to: Apply backward design in order to plan learning goals, assessment, and appropriate scaffolding/support, Describe the meaning of open educational resources, Locate open educational resources relevant to course learning outcomes, Properly attribute works offered under a Creative Commons license, Identify and create works that are accessible to all students, Add a Creative Commons license to your own work and share back with your disciplinary community.